AN EXPERIMENTAL STUDY ON EFFECTIVE UTILIZATION OF BOTTOM ASH (ENNORE) AS FINE AGGREGATE IN CONCRETE UNDER FLEXURE - Kannan, Kai; Kumar, R Vijaya (International Journal of Research -GRANTHAALAYAH, 2017)
Since the construction industry is developing very fast the requirement of concrete and their constituent materials are also increasing day by day. Hence the need becomes in evitable to find various alternate means for the aggregate and accordingly the researchers are going on in this way. But the availability of fine aggregate becomes difficult day by day. Hence the need arises to find alternative for the fine aggregate. The material which is known as bottom ash is available ash waste by-product material from the thermal power plants. In India most of the thermal power plants use wet system for disposal of ash. Bottom ash will be generated as a residue after burning pulverised coal at boiler cyclone and collected from bottom ash hopper located under boiler structure. In this project work the material bottom ash is experimentally analysed and studied for its suitability as replacement as fine aggregate up to (0% to 50%). So far few researchers analysed its suitability as FA by finding the compressive strength of concrete. But in this project work the split tensile strength of concrete and flexural strength of concrete were analysed by replacing bottom ash as fine aggregate.